Comparing Waterbeds and Sand Beds for Cows: A Study at the UF/IFAS Dairy Unit - Klibs N. Galvão; Ori Eizenberg (EDIS)
One important aspect of a cow’s comfort is the type of bedding used. Waterbeds for cows have recently gained popularity because of advertisements, news reports in outlets such as CNN. The UF/IFAS Dairy Unit (DU) provides a good opportunity to compare sand beds and waterbeds at optimal conditions. The dairy has waterbeds installed in one half of the barns and sand beds in the other half. This publication provides a field comparison of waterbeds and sand beds in one herd. We observed that when stalls are maintained at optimal conditions, cows in sand-bedded stalls had decreased incidence of hock lesions and increased stall usage compared to cows in waterbeds. This 5-page fact sheet was written by Klibs N. Galvão and Ori Eizenberg and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, May 2013.